Dopamine control of pyramidal neuron activity in the primary motor cortex via D2 receptors - Vitrac, Clément; Péron, Sophie; Frappé, Isabelle; Fernagut, Pierre-Olivier; Jaber, Mohamed; Gaillard, Afsaneh; Benoit-Marand, Marianne (Frontiers in Neural Circuits, 2014)
The primary motor cortex (M1) is involved in fine voluntary movements control. Previous studies have shown the existence of a dopamine (DA) innervation in M1 of rats and monkeys that could directly modulate M1 neuronal activity. However, none of these studies have described the precise distribution of DA terminals within M1 functional region nor have quantified the density of this innervation. Moreover, the precise role of DA on pyramidal neuron activity still remains unclear due to conflicting results from previous studies regarding D2 effects on M1 pyramidal neurons. In this study we assessed in mice the neuroanatomical characteristics of DA innervation in M1 using unbiased stereological quantification of dopamine transporter-immunostained fibers. We demonstrated for the first time in mice that DA innervates the deep layers of M1 targeting preferentially the forelimb representation area of M1. To address the functional role of the DA innervation on M1 neuronal activity, we performed electrophysiological recordings of single neurons activity in vivo and pharmacologically modulated D2 receptors activity. Local D2 receptors activation by quinpirole enhanced pyramidal neurons spike firing rate without changes in spike firing pattern. Altogether, these results indicate that DA innervation in M1 can increase neuronal activity through D2 receptors activation and suggest a potential contribution to the modulation of fine forelimb movement. Given the demonstrated role for DA in fine motor skill learning in M1, our results suggest that altered D2 modulation of M1 activity may be involved in the pathophysiology of movement disorders associated with disturbed DA homeostasis.